Learning Videos and Geogebra: Do They Really Help Students Solve Their Answers? - Setyaningrum, Agustina; Jaelani, Anton (Jurnal Pendidikan Matematika, 2025)
Multimedia is a combination of various media elements, such as text, images, audio, video, and animation used by teachers to deliver teaching materials effectively and innovatively. There are various types of interactive multimedia that can be used, one of which is that teachers often involve videos and GeoGebra to help students learn mathematics. In practice, this assistance often makes students take a longer path to achieve learning goals. This study provides another perspective to determine the implications of learning videos and GeoGebra in completing answers that help students. With a descriptive method, this study took students as its subjects whose results were analyzed qualitatively using data descriptions, data reduction and presentation of conclusions. It turns out that videos are less able to help students complete their answers and GeoGebra can make students less than optimal in improving their thinking skills. However, the use of learning videos can be used by students to remember continuously to be used as independent learning materials and the use of GeoGebra can be used to correct answers that have been obtained using manual methods.